Blood will tell : a novel - Chavez, Heather (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"From the author of the acclaimed debut No Bad Deed, a twisty novel about the bond between two sisters--and the crimes one covers up to protect the other."--